SmartClip versus conventional twin brackets for initial alignment: is there a difference? - Miles Peter G. (Australasian Orthodontic Journal, 2005)
Objective: To compare the effectiveness of SmartClip brackets and conventional twin brackets for initial alignment of the lower arch.